PENDEKATAN TEKNIK FUZZY TSUKAMOTO UNTUK MENGUKUR KEPUASAN PELANGGAN (STUDI KASUS MARI PHOTO STUDIO) - Geby Gefariosa Manullang (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2021)
Photo studio is one of the businesses in the service sector that always maintains loyalty to customers in order to increase sales and also increase customer satisfaction. By understanding customer needs, wants and demands, it will provide important input for companies to design marketing strategies in order to create satisfaction. for its customers. The method used in this research is the Fuzzy Tsukamoto method which aims to measure the level of customer satisfaction with the Mari Photo Studio Store. Based on sales data from 2018-2021 at the Mari Photo Studio Shop with many packages, including: graduation photo packages, pre-wedding photo packages, wedding photo packages, school photo packages, gold photo packages, and others. Get 70% of customers are satisfied, 20% of customers are quite satisfied, and 10% of customers are not satisfied. The use of the Tsukamoto fuzzy method aims to make it easier to measure customer satisfaction.